Implementation of Automated Test Case Generation in REST API on Android-Based Koperasi Application - Syamsul Mujahidin; M. Reinaldy Hermawan; Chandra Cahyo Utomo (Universitas Bina Darma, 2023)
This study is focused on developing a data collection system to enhance the performance of Koperasi, an organization with complex data collection. An Android application was created to automate the processing of member and transaction data, significantly improving data processing efficiency. However, building a quality system takes time and requires error-free data processing. To achieve this, Automated Test Case Generation with EvoMaster was used to test the REST API and identify errors. The testing process went through several iterations until almost no errors were found. EvoMaster generated over 19.5 million scenarios and found 78 errors in the REST API in 58 hours, which were promptly fixed between iterations. The use of EvoMaster not only reduced development time but also helped maintain code quality.